Perancangan User Experience Aplikasi Pembelajaran Rumus Fisika "Momen Gaya" menggunakan Pendekatan Human Centered Design (HCD) - Fiqih Yanfirdaus Afandi; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The rapid spread of Covid-19 has forced the government to close all schools and recommend online learning at home. Various efforts were made to keep teaching and learning activities running even though there were no face-to-face meetings. online learning is proven to be less effective if applied in learning, and students also cannot interact directly and students also do not understand the material conveyed by the teacher using online applications. Of course, this problem also has an impact on physics subjects. Physics is a branch of science and is a science that develops through scientific steps, starting from determining problems, formulating hypotheses, testing hypotheses through experiments, making conclusions, and discovering theories and concepts. The factor that causes some students not to like physics is from the perspective of students who think that physics only contains formulas or theories to be memorized. If physics is viewed more broadly by students, physics has many concepts that must be understood in depth and physics itself can also be applied in everyday life. One of the chapters or material contained in physics subjects is the moment of force. During a pandemic like this, some students are lazy to learn to open books and try theory and practice it, even though to work on physics problems students have to try and learn the theory and formulas. The need for new learning models that can be done anywhere and anytime. students want new learning via smartphones or tablets so that students can learn anywhere and anytime. To help the learning process, therefore the researcher wants to focus on the process of learning the physics formula about the moment of force as the basis of user experience research. Another goal of this research is to make it easier for students to learn the moment of force chapter by applying visual images to examples of moment of force questions so that students can more easily imagine what questions they will work on.